Sociodemographic factors associated with COVID-19 in-hospital mortality in Brazil. (March 2021) - Peres, I.T.; Bastos, L.S.L.; Gelli, J.G.M.; Marchesi, J.F.; Dantas, L.F.; Antunes, B.B.P.; Maçaira, P.M.; Baião, F.A.; Hamacher, S.; Bozza, F.A.
Abstract: Objectives: The coronavirus disease 2019 (COVID-19) pandemic has highlighted inequalities in access to healthcare systems, increasing racial disparities and worsening health outcomes in these populations. This study analysed the association between sociodemographic characteristics and COVID-19 in-hospital mortality in Brazil. Study design: A retrospective analysis was conducted on quantitative reverse transcription polymerase chain reaction–confirmed hospitalised adult patients with COVID-19 with a defined outcome (i.e. hospital discharge or death) in Brazil. Data were retrieved from the national surveillance system database (SIVEP-Gripe) between February 16 and August 8, 2020. Methods: Clinical characteristics, sociodemographic variables, use of hospital resources and outcomes of hospitalised adult patients with COVID-19, stratified by self-reported race, were investigated. The primary outcome was in-hospital mortality. The association between self-reported race and in-hospital mortality, after adjusting for clinical characteristics and comorbidities, was evaluated using a logistic regression model. Results: During the study period, Brazil had 3, 018, 397 confirmed COVID-19 cases and 100, 648 deaths. The study population included 228, 196 COVID-19–positive adult in-hospital patients with a defined outcome; the median age was 61 years, 57% were men, 35% (79, 914) self-reported as Black/Brown and 35.4% (80, 853) self-reported as White. The total in-hospital mortality was 37% (85, 171/228, 196). Black/Brown patients showed higher in-hospital mortality than White patients (42% vs 37%, respectively), were admitted less frequently to the intensive care unit (ICU) (32% vs 36%, respectively) and used more invasive mechanical ventilation (21% vs 19%, respectively), especially outside the ICU (17% vs 11%, respectively). Black/Brown race was independently associated with high in-hospital mortality after adjusting for sex, age, level of education, region of residence and comorbidities (odds ratio = 1.15; 95% confidence interval = 1.09–1.22). Conclusions: Among hospitalised Brazilian adults with COVID-19, Black/Brown patients showed higher in-hospital mortality, less frequently used hospital resources and had potentially more severe conditions than White patients. Racial disparities in health outcomes and access to health care highlight the need to actively implement strategies to reduce inequities caused by the wider health determinants, ultimately leading to a sustainable change in the health system. Highlights: Analysis of 228, 196 adult hospital admissions for coronavirus disease 2019 in Brazil. The in-hospital mortality rate was 37% (85, 171/228, 196). Sociodemographic variables were strongly associated with in-hospital mortality. Black/Brown patients showed higher in-hospital mortality than White patients. The findings reveal racial disparities on outcomes and access to health care in Brazil.